Evaluating the Availability or not of Electronic Learning Adequacies with Regards the Teaching Staff of the Technical Institute/ Nineveh. A Personal Perspective Approach (NTU journal for Administrative and Human Sciences (JAHS), 2023)
Both of the prevalence and development of electronic learning lead to thenecessity of the availability of the related skills to this type of learning which inturn enables the teaching staff member to be operative and to make full use ofthe system. Based on that, the study aims at acquiring the availability or not ofthese adequacies or sufficiency in electronic learning that should be seized bythe staff members of the technical institute/ Nineveh “based on their ownperspective”. This sufficiency is metered through the following adequacies:Having the computer using adequacy, networks using adequacy, designing andmanaging e-learning adequacy, electronic knowledge adequacy. The study usedthe descriptive analytic approach in processing the collected data which is asample of “37” members of the teaching staff of the institute. The procedurewas to fill a questionnaire disseminated to them through a link over google drivewhich is “https://forms.gle/D7GiLasZTs2paEV68”. In addition, theprogramming statistic aid “SPSS V.25” has been used in analysing data. Thestudy came up with some conclusions, most importantly was the provenavailability of the learning adequacies needed for the teaching staff and thevarying percentage over the availability of these four adequacies within theteaching staff. The study proposed that it is a must to overcome the limitationsover using up to date technologies by the teaching staff alongside withenhancing financial and human resources for better enactment of electroniclearning at the institute.